Analysis of Spun Pile Bearing Capacity Based on SPT Data Using the Luciano Decourt and Tomlinson Methods - Rizwan Aziez Setyawan; Hafiz Hamdani; Heni Pujiastuti; Ahmad Zarkasi (Newinera Publisher, 2026)
Spun pile foundations were used in the construction of the Mayor's Office Building in Jempong Village, Mataram City, West Nusa Tenggara Province, as elements that transfer structural loads to more stable soil. This study aims to analyze the bearing capacity of spun pile foundations manually to obtain the ultimate bearing capacity and allowable bearing capacity values by comparing the Luciano Decourt and Tomlinson methods based on SPT data. Through this analysis, it is hoped that the most efficient and appropriate method for application in the soil conditions in the area can be determined. Based on the calculation results, the Luciano Decourt method produced a bearing capacity and allowable bearing capacity of 137,344 tons and 54,938 tons, respectively, while the Tomlinson method produced a bearing capacity and allowable bearing capacity of 89,489 tons and 35,795 tons, respectively. It can be concluded that the most efficient and appropriate method to use in pile foundation planning for the soil conditions in the area is the Tomlinson method because it produces a more conservative bearing capacity. The use of this conservative bearing capacity can help avoid the risk of foundation failure.